Efektivitas Pelatihan Tenaga Potensi dalam Pelaksanaan Operasi Search and Rescue (SAR) Terhadap Kinerja di Kantor Pencarian dan Pertolongan di Sorong - Budiyani Paramita; Syahruddin Hattab; Muhammad Sawir (Jurnal Ilmu Multidisiplin, 2026)
This study is grounded in the increasing complexity of Search and Rescue (SAR) operations in the Sorong region, which necessitates the readiness of professional, responsive, and well-coordinated human resources. Training for SAR potential personnel constitutes a strategic instrument to enhance such capacity; however, its effectiveness in supporting operational performance requires empirical examination. Accordingly, this research addresses two primary questions: (1) what are the supporting and inhibiting factors in the transfer of training outcomes into actual SAR operations; and (2) how does SAR potential training impact the overall effectiveness of SAR operations. This research employs a qualitative approach with a descriptive-analytical design to examine training effectiveness at the result level. Data were collected through in-depth interviews, direct observation, and document analysis involving training organizers, instructors, and participants. The data analysis utilizes the interactive model of Miles, Huberman, and Saldana, while the theoretical framework is based on Kirkpatrick’s training evaluation model and public value theory to assess the contribution of training to public organizational performance. The findings indicate that the transfer of training in SAR operations is determined by the interaction of individual, organizational, and public policy factors. Supporting factors include instructor quality, relevance of training materials, institutional support, and stakeholder involvement, whereas inhibiting factors encompass limited resources, weak coordination, and the absence of systematic post-training follow-up. Furthermore, the training significantly contributes to improved response time, coordination quality, and rescue success rates. Nevertheless, such effectiveness is conditional and requires consistent integration within policy frameworks, continuous evaluation, and systemic organizational capacity building to generate optimal public value.